Multiplexed High-Throughput Serological Assay for Human Enteroviruses - Saarinen NVV; Lehtonen J; Veijola R; Lempainen J; Knip M; Hyöty H; Laitinen OH; Hytönen VP (MDPI, 2022)
Immunological assays detecting antibodies against enteroviruses typically use a single enterovirus serotype as antigen. This limits the ability of such assays to detect antibodies against different enterovirus types and to detect possible type-specific variation in antibody responses. We set out to develop a multiplexed assay for simultaneous detection of antibodies against multiple enterovirus and rhinovirus types encompassing all human infecting species. Seven recombinant VP1 proteins from enteroviruses EV-A to EV-D and rhinoviruses RV-A to RV-C species were produced. Using Meso Scale Diagnostics U-PLEX platform we were able to study antibody reactions against these proteins as well as non-structural enterovirus proteins in a single well with 140 human serum samples. Adults had on average 33-fold stronger antibody responses to these antigens (p< 10(-11)) compared to children, but children had less cross-reactivity between different enterovirus types. The results suggest that this new high-throughput assay offers clear benefits in the evaluation of humoral enterovirus immunity in children, giving more exact information than assays that are based on a single enterovirus type as antigen.